REVITALISASI WAKAF DI INDONESIA (UIN Sunan Kudus, 2017)
One of the most beneficial teachings for others and the reward will always flow is the provision of places for the benefit of society in general, such as wells, roads, places of worship and so forth. As long as the objects taken benefit still and can be exploited by others, then the perpetrators will always get a reward from the Mercy or who is now better known with the teachings of waqf. Since humans are social beings, it is natural that a problem is solved together. Certain needs are sought to be fulfilled on their own and when it is impossible, the solution is done by others or together, or by those with a high social sense. The cash waqf movement is an extraordinary asset of Muslims if it is managed and developed professionally. This movement should begin immediately without considering anything else that is not a principle. Wakaf cash movement will be more powerful when coupled with the movement of zakah mal.